The The Implementation of Teams Games Tournamet (TGT) Learning Model to Improve the Character of Social Concern and History Learning Achievement - Iwan Prasetiyo; Muhammad Hanif (Jurnal Paradigma, 2026)
The purpose of this study was to determine whether the implementation of the Teams Games Tournament (TGT) Learning Model could improve student learning outcomes and caring character in history subjects. This research was conducted at SMA Negeri 1 Barat, with 36 students from class XI-1. The action research procedure consisted of two cycles. The data collection tools used in this study were lesson plans, student and teacher activity observation sheets, and evaluation test questions. The results of the first cycle of research showed that the average percentage of student learning outcomes increased. In the Pre-Cycle stage, the student's mastery score was 63.89% with an average score of 67.4 in the less category, in Cycle I it was 86.11% with an average score of 73.72 and in Cycle II it was 94.44% with an average score of 84.5 in the good category and achieved maximum mastery. The increase in learning outcomes from the Pre-Cycle stage, Cycle I to Cycle II was 30.55%. Based on the research results above, it can be concluded that the use of the Teams Games Tournament (TGT) learning model can improve learning outcomes and the caring character of grade XI-1 students.